Preliminary research on the receptor–ligand recognition mechanism of umami by an hT1R1 biosensor. Issue 3 (25th February 2019) - Huang, Yulin; Lu, Dingqiang; Liu, Hai; Liu, Suyao; Jiang, Shui; Pang, Guang-chang; Liu, Yuan
Abstract : The biosensor reflecting the linkage of the umami signal during conduction and amplification, and the study on the receptor–ligand recognition mechanism. Abstract : The aim of this study was to determine the interaction between the human umami receptor hT1R1 and a ligand while avoiding the cross-talk among various signal pathways in cells. The hT1R1 was modified and mounted onto a signal amplification system on a glassy carbon electrode surface, and the response current towards four umami ligands (sodium glutamate (MSG), disodium inosinate (IMP), disodium guanylate (GMP), and disodium succinate (SUC)) was measured. The allosteric constants of the receptor–ligand interaction were calculated by the method of sensing kinetics, and the results indicated that the sensing ability of hT1R1 towards the abovementioned four ligands was as follows: GMP > MSG > IMP > SUC. After the analysis of the molecular structure and simulation through the molecular docking model, we have found that hT1R1 is essentially a recognition receptor for the nitrogen signal in the body, and it may recognize the umami substance through its amino group. The new research method developed in this study shows promising application in the mechanism study of signal transduction and drug screening.